The Concept of Good Governance in the Story of Prophet Solomon: A Maqāṣidī Interpretation Analysis of Q.S. An-Naml [27]: 17-44 - Khairul Fikri; Khamim (Elkuator Research and Publication, 2025)
This article examines the institutional model of good governance as illustrated in the story of Prophet Solomon, particularly as conveyed in Q.S. An-Naml [27]: 17–44, through a tafsīr maqāṣidī (purposive exegesis) approach. Unlike previous studies that have primarily focused on either the individual leadership of Solomon or isolated narrative fragments, this research argues that the Qur’an provides a holistic framework for governance—one that encompasses the government, civil society, and the private sector, even if not in the form of modern formal institutions. By employing analyses of both maqāṣid zhāhir (apparent objectives) and maqāṣid bāṭin (hidden objectives), along with Abdul Mustaqim’s concept of ḥifẓ al-dawlah (protection of the state), this study demonstrates that the account of Prophet Solomon exemplifies a governance system that prioritizes the protection of religion, life, and the state, while upholding justice, equality, humanity, moderation, and responsible freedom. These findings emphasize that good governance is not solely the responsibility of the leader; rather, it arises from the synergistic collaboration among various segments of society, all striving to achieve the public good (maṣlaḥah). The contribution of this research lies in presenting a more comprehensive Qur’an-based institutional model of good governance, thereby enriching the discourse on tafsīr maqāṣidī within the study of governance. [Artikel ini mengkaji model kelembagaan good governance yang terkandung dalam kisah Nabi Sulaiman, khususnya dalam Q.S. An-Naml [27]: 17-44, melalui pendekatan tafsīr maqāṣidī. Berbeda dengan kajian sebelumnya yang lebih berfokus pada kepemimpinan individu atau fragmen kisah, penelitian ini berargumen bahwa Al-Qur'an menawarkan kerangka tata kelola pemerintahan yang holistik, melibatkan pemerintah, masyarakat madani, dan sektor swasta, meskipun tidak dalam bentuk kelembagaan formal modern. Dengan menggunakan analisis maqāṣid zhāhir dan maqāṣid bāṭin, serta konsep ḥifẓ al-dawlah dari Abdul Mustaqim, penelitian ini menemukan bahwa kisah Nabi Sulaiman mengilustrasikan sebuah sistem pemerintahan yang mengutamakan perlindungan agama, jiwa, dan negara; menegakkan keadilan, kesetaraan, kemanusiaan, moderasi, serta kebebasan yang bertanggung jawab. Temuan ini menyoroti bahwa good governance bukan hanya tanggung jawab pemimpin, melainkan hasil kolaborasi sinergis antara berbagai komponen masyarakat yang bertujuan mencapai maṣlaḥah. Kontribusi penelitian ini adalah menyajikan model kelembagaan good governance berbasis Al-Qur'an yang lebih komprehensif, serta memperkaya diskursus tafsīr maqāṣidī dalam studi tata kelola pemerintahan.]